IoT-Based System for Pothole Mapping - Dwiandharu, Muhammad Andika Naufan; Aulia, Danny; Wisnutama, William Wafi; Pramudita, Aloysius Adya; Ryanu, Harfan Hian; Widhi Prabowo, Vinsensius Sigit (Universitas Telkom, 2024)
Technology development allows various kinds of technology to provide convenience and better services. One of them is the development of technology with the Internet of Things. In this research, we have developed a system to detect and map damaged road conditions to give road users a better experience. The user is expected to use this system to collect data. Detection is done using an accelerometer sensor that estimates the speed of a vehicle. In the process of pothole detection, the accelerometer checks the value of each x, y, and z axis. When data meets the axis value, it is taken by Arduino and sent to the Raspberry Pi. Raspberry Pi, which is an integration of systems, processes data and classificates data. Also, Raspberry Pi enables GPS and camera to collect data in visual form. Data that has been processed, sent to the database to be displayed on the dashboard of application. The system was tested along Jalan Radio Palasari, Bandung Regency. From experiments that have been carried out by collecting 50 data, it is known that the delay in sensor detection is set for approximately one minute with a sending delay to the database of six seconds. The accuracy of data in detecting and mapping only differs by 3-6 meters from the real pothole road.